A biopsy‐needle compatible varifocal multiphoton rigid probe for depth‐resolved optical biopsy. Issue 1 (5th September 2018) - Li, Ang; Hall, Gunnsteinn; Chen, Defu; Liang, Wenxuan; Ning, Bo; Guan, Honghua; Li, Xingde
Abstract : In this work, we report a biopsy‐needle compatible rigid probe, capable of performing three‐dimensional (3D) two‐photon optical biopsy. The probe has a small outer diameter of 1.75 mm and fits inside a gauge‐14 biopsy needle to reach internal organs. A carefully designed focus scanning mechanism has been implemented in the rigid probe, which, along with a rapid two‐dimensional MEMS scanner, enables 3D imaging. Fast image acquisition up to 10 frames per second is possible, dramatically reducing motion artifacts during in vivo imaging. Equipped with a high‐numerical aperture micro‐objective, the miniature rigid probe offers a high two‐photon resolution (0.833 × 6.11 μm, lateral × axial), a lateral field of view of 120 μm, and an axial focus tuning range of 200 μm. In addition to imaging of mouse internal organs and subcutaneous tumor in vivo, first‐of‐its‐kind depth‐resolved two‐photon optical biopsy of an internal organ has been successfully demonstrated on mouse kidney in vivo and in situ . Abstract : Optical biopsy calls for label‐free, in vivo and in situ interrogation of tissue at histopathological resolution. Considerable efforts have been made for enabling multiphoton microscopy imaging of internal organs, but they all involved surgical elevation of target organs to reduce motion artifact and most lacked depth scanning, which fell short of the in situ requirement for optical biopsy. In this work, we report a biopsy‐needle compatible rigid probe, capable of performing three‐dimensional two‐photon optical biopsy.